A Possible Indicator of Oxidative Damage in Smokers: (13Z)-Lycopene? - Daniel L. Graham; Mario Lorenz; Andrew J. Young; Gordon M. Lowe (MDPI AG, 2017)
In vitro, the gaseous phase of cigarette smoke is known to induce both isomerization and degradation of dietary carotenoids, such as β-carotene and lycopene. However, the effects of cigarette smoke on the composition of circulating lycopene in vivo are not well understood. In this study, we examined the lycopene profiles of plasma from non-smokers and smokers. No oxidative intermediates of lycopene that have been observed previously in vitro were detected in the plasma, but evidence of isomerization of the carotenoid was seen. Four geometric forms of lycopene were detected in the plasma of both smokers and non-smokers, namely the (5Z), (9Z), (13Z) and (all-E) forms. The relative amounts of these isomers differed between the two cohorts and there was a significant difference (p < 0.05) between smokers and non-smokers for the ratio of total-Z:all-E lycopene, and in the relative amounts of (13Z) and (all-E)-lycopene. The ratio of (all-E):(13Z)-lycopene was 0.84:1.00 in smokers compared to 1.04:1.00 in non-smokers. In smokers, the (13Z)-isomer was generated in preference to the more thermodynamically stable (5Z) and (9Z)-isomers. This mirrors the scenario seen in vitro, in which the formation of (13Z)-lycopene was the main isomer that accompanied the depletion of (all-E) lycopene, when exposed to cigarette smoke. The results suggest that the relative amount of (13Z)-lycopene could be used as an indicator of oxidative damage to lycopene in vivo.